Autopsy findings in sudden cardiac death victims at a tertiary health care centre - Patil, Suwarna; Zamad, Prashant; Jungare, Ajay; Nasare, Anuja; Umap, Pradip; Rudra , Pradip (Journal of Indian Academy of Forensic Medicine, 2021)
In the present era there is a transition of the cause of death from communicable to non-communicable diseases (NCD) due to changing life style as well as environmental factors. Sudden cardiac death (SCD) is one of the most common NCD and an important mode of death all over the world. Hence, the accurate diagnosis of the causes of SCD is now of particular importance. Pathologists are solely responsible for determining the precise cause and mechanism of sudden death through autopsy. In present study we included 260 cases with age ranging from 1 to 80 years. 75 (28.8%) of these 260 cases showed cardiovascular lesions with a male: female ratio of 14:1. Coronary artery disease with or without other associated lesions was the most frequent finding (90.7%). Other causes included atherosclerosis of aorta, myocardial infarction (MI), myocarditis and cardiomyopathy. Rare findings were left atrial myxoma and malignant mesothelioma. Though predominantly affected age group was 41-50 years, there was significant number of affected young patients as well. Thus, this study highlights the importance of screening the population from young age itself for cardiovascular diseases to reduce related morbidity and mortality.